A bibliometric and content analysis of strategy-based instruction and self-regulated learning in second or foreign language teaching from 1994 to 2024 - Ruihua Chen; Xiao Wang; Kezhen Zhu (Frontiers in Psychology)
IntroductionThis study aims to explore the research themes and identify gaps on strategy-based instruction (SBI) and self-regulated learning (SRL) in language education, spanning the period from 1994 to 2024. Using a systematic review methodology, this study examines the empirical research in the SBI and SRL in English as second or foreign language teaching contexts published during this period.MethodsThe review employs both bibliometric and content analysis to reveal current trends to facilitate understanding of the role of SBI and SRL in teaching practices. Using VOSviewer, a keyword co-occurrence analysis was conducted on 35 selected papers from Web of Science and Scopus databases.ResultsThe bibliometric analysis reveals a shift in research focus from student self-development to the impact of learning strategies on students’ learning achievement. The content analysis indicates that studies have focused on writing instruction, enhancement of learners’ SRL, and technology-assisted instruction, with the latter showing potential for developing students’ SRL strategies.DiscussionOverall, this study highlights the significance of integrating SBI and SRL into language education, offering insights into writing instruction, technology-assisted learning, and SRL development. It emphasizes the need for future research to explore specific skills, technology-assisted learning, longitudinal mixed-methods approach. This paper aims to serve as a useful resource for researchers and practitioners involved in research related to EFL and ESL teaching.